In-Hospital Mortality of Disseminated Tuberculosis in Patients Infected with the Human Immunodeficiency Virus - Rodrigo Pires dos Santos; Caroline Deutschendorf; Karin Scheid; Luciano Zubaran Goldani (Clinical and Developmental Immunology)
Background. Tuberculosis (TB) is a cause of significant morbidity and mortality in patients with AIDS. The goal of our study was to determine predictors of in-hospital mortality in patients with AIDS and disseminated tuberculosis in a middle-income country. Material and Methods. We conducted a retrospective cohort study in a tertiary care center, for patients with AIDS in southern Brazil. From 1996 to 2008, all patients with the diagnosis of disseminated TB were included. Results. Eighty patients were included. In-hospital mortality was 35%  (N=28). On multivariate Cox regression analysis, low basal albumin (P<.01) was associated with death, and fever at admission was related to better survival (P<.01). Conclusion. Albumin levels or fever are independent predictors of survival in patients with HIV and disseminated TB. They can serve as indirect markers of immunodeficiency in patients with disseminated TB and AIDS.